Reproductive biology and population dynamics of Crassostrea (Magallana) saidii Wong & Sigwart, 2021 in the estuary of Sungai Muar, Johor, Malaysia - Barman, Arun Chandra (2022)
Crassostrea (Magallana) saidii Wong & Sigwart, 2021 was recently described as a new oyster species to science. It is an endemic species with its only known distribution limited to Muar estuary, Malaysia, and has been actively harvested from its natural habitat by the locals since at least 1858. This latest taxonomic development warrants a closer look into the reproductive biology and population structure of C. (M.) saidii, which was thought to be a morph-variant of other oyster species in the same vicinity but has a widespread distribution in the country. Additionally, concern arises as the population size is believed to reduce, implicating local fisheries. However, the objectives of this research were to provide information on the reproductive biology and population dynamics of C. (M.) saidii from the estuary of Sungai Muar, Johor, Malaysia. The first study was conducted to evaluate the sex ratio and reproductive phenology of C. (M.) saidii through gonad histology and biometry. Samples of 30 individual oysters were taken monthly from November 2018 to January 2020 from the sole population at Sungai Muar estuary, Johor, Malaysia. Histology revealed that among 450 oysters analyzed, male, female, hermaphrodite, and undifferentiated individuals were at 35.33%, 58%, 1.56%, and 5.11%, respectively. Overall male and female sex ratio was 1:1.64, with female numbers significantly higher. However, the sex ratio was different when the oysters were divided into groups according to shell height (SH) in intervals of 10 mm. The proportion of males decreased with increasing shell height, although the shell height of males and females greatly overlapped. The sex reversal pattern of the oyster might go from male to female and again female to male, with an indicator of rhythmical hermaphroditism. In the current study, statistically significant differences in the size of oogenic cells (mature > maturing > degenerating > immature > oogonia) and the spermatogenic cells (spermatogonia > spermatocyte > spermatid > spermatozoa) were observed. Gametogenesis occurred around the research period with remarkable time-based variations. The oyster spawned over the study period, with peaks in April (2019) and November (2018 and 2019). Condition index (CI) ranged from 70.03 (October 2019) to 31.90 (April 2019), exhibiting four peaks when most of the oysters were maturing stage and subsequently decreases in CIs indicating spawning. Three distinct peaks in maturity indices (MIs) of the oyster were noted during March, August, and October 2019, when the majority of oysters were mature and ready for spawning. The second study was carried out to correlate environmental variables with the gonadal maturity of C. (M.) saidii. Thirty oysters were taken monthly from November 2018 to January 2020 from the Sungai Muar estuary. The findings showed that there was no significant correlation between water quality parameters like temperature, salinity, pH and total suspended solids, whereas a significant positive correlation was identified between upstream rainfall and spawning gonad (r2 = 0.534, p < 0.05). A multiple regression between spawning individuals and environmental variables (temperature, pH, salinity, total suspended solids, and rainfall) indicated that rainfall (beta = 0.535, p < 0.05) triggered the spawning of the oyster C. (M.) saidii in the estuary. The effects of salinity on the gonadal maturation of the oyster were observed in a controlled environment, conducted in the International Institute of Aquaculture and Aquatic Sciences (I-AQUAS), Universiti Putra Malaysia (UPM), between December 2020 and February 2021 with a duration of 60 days. The oysters were conditioned using three salinities of 10, 15, and 20 ppt. The study revealed that all the salinities were suitable for the maturation of the gonad of the oysters after 30 days and 60 days of the observation. The condition index was not affected by the salinity concentrations over the study period. The species’ size-weight relationship and population structure were assessed in 2019 to determine its population dynamics. Results indicated that the gradient of the size-weight equation (b = 2.5422) was significantly different (t = 38.93, p < 0.01) from the isometric value (3), indicating negative allometric growth of the C. (M.) saidii in the estuary. The asymptotic shell height (SH∞) and growth coefficient (K) were observed at 15.23 cm and 0.69 per year, respectively. The maximum observed height and predicted extreme height was 14.50 cm and 14.72 cm, respectively. The calculated growth performance index (φ/) was 2.204. The annual total mortality (Z) using the length-converted catch curve was calculated at 3.02, annual fishing mortality (F) at 1.27, and annual natural mortality (M) at 1.75. The recruitment pattern of the oyster showed continuous recruitment, with two peaks over the study period. The exploitation level (E) of the oyster was computed at 0.42, while the allowable limit of exploitation (Emax) was 0.782 for the highest yield. The current exploitation level (E = 0.42) indicates that the oyster stock was exploited at almost the optimum (E = 0.5) from the estuary. The understanding of the reproductive biology and population dynamics could provide information for optimal and accurate management of the natural population of oyster C. (M.) saidii in its sole habitat. The identification of maturation and spawning season of this species will allow their conservation through aquaculture approach while reducing commercial pressures from the natural stock.